2019
DOI: 10.3390/informatics6010010
|View full text |Cite
|
Sign up to set email alerts
|

ETL Best Practices for Data Quality Checks in RIS Databases

Abstract: The topic of data integration from external data sources or independent IT-systems has received increasing attention recently in IT departments as well as at management level, in particular concerning data integration in federated database systems. An example of the latter are commercial research information systems (RIS), which regularly import, cleanse, transform and prepare the analysis research information of the institutions of a variety of databases. In addition, all these so-called steps must be provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The researchers presented new techniques of data cleansing which can be applied to research information. On the other hand, the research did not touch the Data Ops technique (Azeroual et al, 2019b).…”
Section: Paper Finding Discussionmentioning
confidence: 91%
“…The researchers presented new techniques of data cleansing which can be applied to research information. On the other hand, the research did not touch the Data Ops technique (Azeroual et al, 2019b).…”
Section: Paper Finding Discussionmentioning
confidence: 91%
“…To address these challenges during information integration, the solution is to implement the ETL process, information integration methods and techniques. The investigations clearly showed in the related paper [8] that during the transformation phase of the ETL process the processing of the internal and external data sources should take place. This enables the cleaning, transformation, harmonization and merging of the data which have already been consolidated in the RIMS in order to create new quality of information that may be of particular importance to an institution.…”
Section: Discussionmentioning
confidence: 97%
“…Since the RIMS obtains its information or data from several heterogeneous sources, the data must be converted into a uniform internal format. For this, the following transformations, which can be summarized under the term of "data migration", are required [7,8] [9], the following problem areas may also arise during the transformation phase. These were considered and investigated with examples in the context of RIMS, which can be found in the related paper [8], such as: These so-called errors or problem areas should be eliminated in order to achieve the highest possible data quality.…”
Section: Transformation Of Research Informationmentioning
confidence: 99%
“…The Quality Objective Matrix (QOX) is one of the quality measures of data and information that can be used to examine the performance of relevant data and information to ensure the effectiveness of ETL workflow [1,4,[7][8][24][25]. Previous studies identified four dimensions of QOX: accuracy, completenes, scalability, and efficiency [7][8][30][31][32][33] as presented in Table 1. The accuracy measures the correctness of data transformation in terms of right formats, data type, and data length [7].…”
Section: Qualification Objective Matrix (Qox)mentioning
confidence: 99%